(untitled) (Global Journal of Science Frontier Research, 2025)
This paper presents an incontrovertible fact-based framework that fundamentally challenges the age-old assumptions of classical mechanics particularly the notions of absolute time and space We demonstrate with mathematical rigor and empirical clarity that these assumptions do not hold when subjected to rigorous analysis of real-world phenomena especially under extreme conditions Our new model of space time and motion provides a correct reliable and comprehensive understanding of the universe - one that aligns seamlessly with the most accurate observations and leaves no room for doubt Through this work we reshape our understanding of the cosmos and offer humanity an unshakable foundation for future advancements in science